UKURAN PERUSAHAAN MEMODERASI HUBUNGAN FINANCIAL DISTRESS DAN AUDITOR SWITCHING PADA LAMANYA PUBLIKASI LAPORAN KEUANGAN - Yasa, I Made Dwipayana; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024, 2024)
This study aims to determine the effect of financial distress and auditor switching on the length of time for publication of financial report with firm size as a moderating variable. The research was conducted on property and real estate sector companies on the IDX for the 2017-2021 period. The population of this study is all property and real estate companies listed on the IDX in 2017-2021 which submitted annual reports of 80 companies. The number of samples used were 45 companies with 193 observational samples. The data analysis technique used is Moderated Regression Analysis. The results of the study show that financial distress has no effect on the length of time for publication of financial report. Auditor switching has a positive effect on the length of time for publication of financial report. Firm size is not able to moderate the effect of financial distress on the length of time for publication of financial report but is able to moderate the effect of auditor switching on the length of time for publication of financial report.